Luteal Phase Stimulation in the Same Cycle Is an Effective Strategy to Rescue POSEIDON Poor Responders with No Embryos after the First Follicular Stimulation - Abha Majumdar; Gaurav Majumdar; Neeti Tiwari; Anu Singh; Shweta Mittal Gupta; Ruma Satwik (Journal of Human Reproductive Sciences)
Background: Poor responders may benefit from recruiting a ‘second wave’ of antral follicles within the same cycle. This concept forms the basis of double stimulation which has been named as ‘DuoStim’. This protocol involves ovarian stimulation in both follicular and luteal phases with egg retrieval in each phase, respectively, to increase the number of oocytes and embryos in one menstrual cycle. This can be considered a potentially valuable option for women with poor ovarian reserve/response to maximise the number of oocytes retrieved in a single ovarian cycle in the shortest possible time. Aims: The aim of this study was to evaluate the efficacy of the DuoStim protocol in women classified as POSEIDON poor responders undergoing in vitro fertilization by comparing the embryological outcomes between the follicular and luteal phase stimulations in the same menstrual cycle. Settings and Design: This was a retrospective cohort study of 131 patients who enrolled to undergo DuoStim cycles from January 2021 to Sept. 2022, at a IVF center in a tertiary care hospital. Materials and Methods: The follicular phase stimulation used a standard antagonist protocol for the first oocyte retrieval. Thereafter, the luteal phase stimulation was started 3 days after the first retrieval, with the same dose of gonadotropin along with a daily 10 mg medroxyprogesterone acetate tablet, followed by a second oocyte retrieval. Blastocysts produced in both the phases were subsequently vitrified. Statistical Analysis Used: The paired t-test was used for comparing means and 95% confidence intervals (CIs) for different parameters. McNemar’s test was used to compare paired proportions. The analysis was conducted using R statistical environment 4.2. Results: The mean number of oocytes retrieved and the mean number of utilizable blastocysts frozen per stimulation cycle were found to be significantly higher in the luteal phase as compared to the follicular phase (5.71 ± 3.95 vs. 4.87 ± 2.79, P = 0.02, and 1.43 ± 1.22 vs. 0.95 ± 1, P = 0.001, respectively). However, the mean fertilization rate and the mean blastocyst utilization rate were found to be similar between both the phases. The length of stimulation was found to be approximately 3 days longer in the luteal phase (12.63 ± 2.43 vs. 9.75 ± 1.85, P = 0.001). Overall, the odds of obtaining a usable blastocyst in the luteal phase was found to be significantly higher than in the paired follicular phase (73.9% vs. 57.7%, P = 0.012, odds ratio: 2.286 [95% CI: 1.186–4.636]). Also importantly, the luteal phase stimulation was able to rescue 68% (32/47) of patients where no blastocysts were formed in the follicular phase. Conclusion: Our data demonstrate that in women with poor reserve, the addition of luteal stimulation could increase the chances of achieving a pregnancy by significantly increasing the number of eggs and transferable embryos per menstrual cycle compared to follicular stimulation alone. Furthermore, luteal phase stimulation in the same cycle proved to be an effective strategy to rescue POSEIDON poor responders with no embryos after the first stimulation.